Fintech Adoption and Project Efficiency in Pakistan: Examining the Role of Risk Management and Trust within Organizations - Syed Muhammad Abdullah; Muhammad Adnan (Indus Journal of Social Sciences, 2025)
Aim: In the rapidly transforming financial and technological landscape, the FinTech adoption has become critical for ensuring efficiency in project-based environments. This study seeks to explore the intricate relationship between Risk Management, Organizational Trust, and FinTech Adoption, and how these variables collectively influence Project Efficiency within Pakistani FinTech firms. The investigation aims to uncover the mechanisms through which internal organizational capabilities foster digital adoption and operational excellence. Methodology: The data for this study were systematically gathered from employees working in various FinTech firms across Pakistan. These respondents were primarily engaged in project planning, execution, risk oversight, and digital transformation roles. A structured, self-administered questionnaire consisting of 191 items was used for data collection. A total of 400 questionnaires were distributed using a convenience sampling method, out of which 191 valid responses were retained for final analysis. The data was analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) technique to assess the strength and direction of relationships among the proposed constructs. Findings: The results confirm that both risk management and organizational trust have significant and positive effects on FinTech Adoption. Additionally, FinTech Adoption plays a strong mediating role in the relationship between these two independent variables and Project Efficiency. This indicates that without adequate trust and risk governance, digital tool implementation may fall short in delivering desired project outcomes. The findings offer robust empirical support for seven of the eight proposed hypotheses. Implications: The study offers valuable insights for FinTech leaders, project managers, and policy advocates by emphasizing the strategic importance of cultivating organizational trust and formalizing risk management systems to accelerate FinTech adoption. These findings reinforce the need for tailored interventions in emerging economies like Pakistan, where digital transformation efforts are growing but often lack structural support.